PENGARUH PENGELUARAN PEMERINTAH DAN JUMLAH TENAGA KERJA TERHADAP PERTUMBUHAN EKONOMI DI KOTA PONTIANAK - B01111031, Rendi Perdiyanto (Jurnal Curvanomic, 2017)
AbstractThis study entitled "Analysis of Effect of Government Spending And Labor AgainstEconomic Growth Pontianak. The research objective was to determine the effect of the analysisof labor and government expenditure in Pontianak on economic growth in Pontianak.Government expenditure consists of direct and indirect expenditures, which is one of thegovernment's fiscal policy and economic growth through the GDPKeywords: government spending, employment and economic growth.